PENERAPAN MODEL PEMBELAJARAN AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV SD NEGERI 125 PEKANBARU - Rohani Rohani '; Otang Kurniaman Otang Kurniaman; Eddy Noviana Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Background of the problem in this study is the low of speaking skills Elementary School fourth grade students 125 pekanbaru, the average grade62,95,. Of it is found that the speaking skills of students is low. This study aims to improve learning outcomes speaking skills Elementary School Fourth grade students 125 Pekanbaru applying learning model Active, Creative, Effective, and Fun (PAKEM). The research was conducted o March 31, 2015 to April 27, 2015 that carried as much as cycle. This thesis present speaking skills the results obtained from the study before action replay value with an average of 62,95, an increase in the first cycle with an average of 63,63. I the second cycle increased by an average of 80,30. Teacher activity the first cycle and and the first meeting of 58,33% the second meeting increased to 62,50%. The first meeting of the second cycle of 75% and the second meeting increased to 83,33%. Student activity the fisrt cycle the fisrt meeting with an average of 57,14 and a second meeting increased to 58,33%. At the first meeting of the second cycle with an average of 79,17% and at the second meeting increased to 83,33%. From the results of studies in fourth grade Elemetary School 125 Pekanbaru prove that the application of learning model active, Creative, Effective, and Fun Elementary School Fourth grade students 125 Pekanbaru.Keywords: Model Active, Creative, Effective, and Fun (PAKEM), speaking skills